Hike - Oswald, Pete (Somerville, Massachusetts : Candlewick Press, 2020)
A father and child head out on a hike, keeping a cherished family tradition alive.
Keywords: Fathers and sons -- Juvenile fiction; Hiking -- Juvenile fiction; Fathers and sons -- Fiction; Hiking -- Fiction; Picture books; Stories without words